CONSTITUTIVE MODEL FOR TIMBER FRACTURE USED FOR FE SIMULATION OF LVL ARCH - Eliška Šmídová (Acta Polytechnica CTU Proceedings, 2018)
Non-linear finite element simulation of four-point bending test of a small-size arch is described in this paper. The arch of 780mm span is made of Yellow Poplar (Liriodendron tulipifera) laminated veneer lumber (LVL) and it is manufactured with a through crack parallel to fibers in the middle of its crown. 2D homogeneous orthotropic constitutive model of tensile and shear fracture in timber that has been recently developed and implemented into ATENA® element software by the authors is used for the numerical calculation. Both standard and compact tension (CT) test results are used for the material model calibration. Results show that the model successfully reproduces the increasing part of the load-displacement response. Furthermore, the model can capture the most distinctive features of the crack pattern.